Innovation barriers as triggers of firms' eco-innovations: the mediating role of public and market knowledge sourcing - Dmytrenko, Denys; Rehman, Fazal ur; Prokop, Viktor (Routledge, 2024)
This study expands the existing knowledge about the impact of innovation barriers on firms and tests whether such barriers stimulate their environmental behaviours. For these purposes, we focus on the specific region of Central Europe, which was considered lagging in previous years. It was caused, on the one hand, by the lower innovation performance of firms and states in comparison with their western neighbours, but also due to a lower environmental perception on the part of the whole society. By using data on 14,808 firms from three Central European countries (Czech Republic, Slovakia, and Hungary) and the Partial Least Square Structural Equation Modelling (PLS-SEM) method, this study contributes to the ongoing debate regarding the eco-innovation performance of the Central European territory, where such analyses are still rare. Our results show that firms facing innovation barriers tend to create eco-innovations. We confirm our expectation that Central European firms depend on external sources of knowledge acquired on the market. Moreover, we show that even public knowledge resources obtained from universities and research institutions support the creation of eco-innovations. These results allow us to propose several implications for practitioners and policymakers.
Inovační bariéry jako spouštěče ekologických inovací firem: zprostředkovatelská role veřejného a tržního získávání znalostí
Keywords: Innovation barriers; eco-innovation; Central Europe; knowledge; R&D; Inovační bariéry; ekologické inovace; střední Evropa; znalost; R&D